Muzzle [videorecording (DVD)] - Stalberg, John, Jr; Eubank, Carlyle; Eckhart, Aaron; Mitchell, Penelope; Tinoco, Diego; Johansson, Paul, 1964-; Smithson, Kyle; Reynolds, Delissa; Lang, Stephen, 1952-; Gallister, Paul, 1984- (RLJE Entertainment, Inc., 2023)
After his dog is killed in Skid Row, Jake Rosser plummets deep into a sinister underworld to uncover the truth about who may be responsible.